Nano-particle, preparation method thereof and application of nano-particle to fluorescent ink

By surface modification of the upconversion nanoparticles doped with lanthanide rare earth, nanoparticles used for fluorescent ink were prepared, which solved the low luminous intensity, poor thixotropy performance, and poor printing adaptability of the existing anti-counterfeiting technology. The problem of this has achieved efficient and environmentally friendly fluorescent ink preparation.

CN119391401AActive Publication Date: 2025-02-07SHAANXI DADI IND CO LTD OF CHINA NAT NUCLEAR +1

Patent Information

Application Number
CN202411194531.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-02-07
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The existing anti-counterfeiting technology has low luminous intensity, poor thixotropic performance, poor printing adaptability, and high environmental pollution.

Method used

By surface modification of polyacrylic acid to the lanthanide rare earth doped NaYF4 up-converting nanoparticles, a nanoparticle was prepared, which was used to prepare vegetable oil-based fluorescent inks with high fluorescence intensity, stability and environmental protection.

Benefits of technology

The high fluorescence intensity, stability and environmental protection of fluorescent inks are achieved, and the printing adaptability and thixotropic properties of the ink are significantly improved, which is suitable for different printing methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391401A_ABST
    Figure CN119391401A_ABST
Patent Text Reader

Abstract

The invention provides a nanoparticle, a preparation method thereof and application of fluorescent ink, the preparation method of the nanoparticle comprises the following steps: polyacrylic acid is used for surface modification of lanthanide rare earth doped NaYF4 up-conversion nanoparticles, and the mass ratio of polyacrylic acid to the lanthanide rare earth doped NaYF4 up-conversion nanoparticles is 1: (5-50). The nano material has the characteristics of small size, large specific surface area and existence of a large number of rare earth ion luminescence centers on the surface, and also has the advantages of high luminescence efficiency and strong fluorescence intensity. When the nanoparticles are used for preparing plant oil-based fluorescent ink, the obtained anti-forgery ink has the advantages of no organic solvent volatilization, no radioactive element, no toxicity, no harm and good environment-friendly effect; the ink is uniform, stable and high in acid and alkali resistance, and meets performance standards of related industries; and the fluorescent powder also has the advantages of high fluorescence intensity, good color rendering property, beautiful printed pattern effect and sustainable luminescence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to ink preparation technology, and in particular to nanoparticles, a preparation method thereof and applications of fluorescent ink. Background Art

[0002] Different anti-counterfeiting technologies, including holograms, watermarks, gravure printing, microprinting, and fluorescent ink printing, have been developed and integrated into documents, certificates, banknotes, product labels, and other certifications to combat counterfeit goods and applications. In the past two decades of economic development, a variety of mature anti-counterfeiting technologies have emerged on the market, mainly including fluorescent anti-counterfeiting technology, laser holographic anti-counterfeiting technology, multimedia anti-counterfeiting technology, radio frequency identification anti-counterfeiting technology, biological anti-counterfeiting technology, and nuclear track anti-counterfeiting technology. Thanks to the unique chemical, physical, and optical properties of luminescent materials, they are usually made into luminescent security inks, which are further used in different printing methods (such as stamp printing, screen printing, and inkjet printing) to produce highly complex and high-resolution luminescent patterns for anti-counterfeiting applications. Among them, inkjet printing of luminescent security inks is superior to other printing methods because of its low reagent consumption, direct and high-throughput patterning capabilities, difficulty in replication, and ease of authentication. Therefore, inkjet printing of fluorescent anti-counterfeiting inks enables the development of large-scale and complex anti-counterfeiting technologies. On the other hand, inkjet printing requires that the fluorescent pigments in the fluorescent inks are in the nanometer size range to avoid any potential clogging of the inkjet printing nozzles. Conventional luminescent security inks printed by inkjet are usually made of down-conversion fluorescent nanomaterials, such as photochromic compounds, semiconductor quantum dots, carbon quantum dots, and metal-organic frameworks. These down-conversion-based luminescent materials and inks can be excited by ultraviolet light and thus used as anti-counterfeiting banknotes, certificates, and documents. However, these down-conversion fluorescent materials usually have photobleaching defects, high toxicity, and broad emission bands. More importantly, anti-counterfeiting technology based on down-conversion fluorescent materials has been well studied and is relatively easy to be cracked by skilled counterfeiters. Summary of the invention

[0003] The present invention aims to provide a nanoparticle and a preparation method thereof and use of fluorescent ink to solve the problems of existing anti-counterfeiting technology such as low luminous intensity, poor thixotropic performance, poor printing adaptability, and greater environmental pollution.

[0004] In order to solve the above-mentioned prior art problems, the technical solution adopted by the present invention is as follows:

[0005] In a first aspect, the present invention provides a method for preparing nanoparticles, comprising: surface modifying lanthanide rare earth-doped NaYF4 upconversion nanoparticles with polyacrylic acid, wherein the mass ratio of the lanthanide rare earth-doped NaYF4 upconversion nanoparticles to the polyacrylic acid is 1:5 to 50.

[0006] Preferably, the surface modification comprises the following steps:

[0007] Step 1, adding the lanthanide rare earth doped NaYF4 upconversion nanoparticles to solvent 1 to obtain an upconversion nanoparticle solution, and dissolving polyacrylic acid in solvent 2 to obtain a polyacrylic acid solution;

[0008] Step 2: mixing the upconversion nanoparticle solution and the polyacrylic acid solution at 20-30° C. for reaction for 20-30 hours, separating the solid after the reaction, and drying to obtain the nanoparticles.

[0009] Preferably, the first solvent is selected from at least one of cyclohexane, n-hexane, dimethylformamide, dimethyl carbonate and dichloromethane; and / or the second solvent is selected from at least one of ethanol, acetone and isopropanol.

[0010] Preferably, in step 2, the volume ratio of the upconversion nanoparticle solution to the polyacrylic acid solution is 1:2-4; and / or, the method for separating the solid is centrifugation, preferably centrifugation at 12000-15000 rpm for 5-15 min; and / or, the method for drying is vacuum drying, preferably drying at 50-70°C and a vacuum degree of not less than 0.05 MPa for 2-3 h.

[0011] Preferably, the method for preparing the lanthanide rare earth doped NaYF4 upconversion nanoparticles comprises the following steps:

[0012] (1) preparing a rare earth oleate precursor: mixing yttrium salt, rare earth metal salt, and oleic acid compound in solvent three, heating and reacting to obtain a rare earth oleate precursor; and

[0013] (2) Preparation of lanthanide rare earth doped NaYF4 upconversion nanoparticles: The rare earth oleate precursor, oleic acid, octadecene, ammonium fluoride and a catalyst are mixed and reacted. After the reaction is completed, a precipitant is added to the system and a solid is separated to prepare lanthanide rare earth doped NaYF4 upconversion nanoparticles.

[0014] Further preferably, in step (1), the yttrium salt is selected from YCl3; the rare earth metal salt is selected from YbCl3 and / or ErCl3; the oleic acid compound is selected from one of sodium oleate, potassium oleate, oleic acid and egg yolk lecithin; more preferably, the molar ratio of the yttrium salt, the rare earth metal salt and the oleic acid compound is: 1-7:0.1-1.5:5-7.

[0015] Further preferably, in step (1), solvent three is a mixture of water and at least one selected from methanol, ethanol, isopropanol and ethylene oxide, and at least one selected from n-hexane, n-heptane, isohexane and petroleum ether; more preferably, solvent three is a mixture of deionized water and at least one selected from methanol and ethanol, and at least one selected from n-hexane and isohexane; most preferably, solvent three is a mixture of deionized water, ethanol and n-hexane in a volume ratio of 1 to 2:1 to 2:1 to 4.

[0016] More preferably, in step (1), the heating reaction temperature is 60 to 80° C., preferably 70±5° C.; and / or the reaction time is 3 to 6 hours, preferably 4 to 5 hours.

[0017] More preferably, in the step (2), a rare earth oleate precursor, oleic acid and octadecene are mixed to obtain a first mixed solution, and ammonium fluoride and a catalyst are added to solvent four to obtain a second mixed solution, and then the two mixed solutions are mixed and reacted; preferably, the molar ratio of the rare earth oleate precursor, ammonium fluoride and the catalyst is 1-10:2-12:1-15.

[0018] Preferably, the catalyst is sodium hydroxide or potassium hydroxide; and / or, the solvent is selected from at least one of methanol, ethanol, dichloromethane and chloroform.

[0019] More preferably, in the step (2), the control procedure of the mixed reaction includes: during the addition of the mixed solution of ammonium fluoride, the catalyst and the solvent four, the system temperature is 40-60°C, most preferably 50±5°C, and / or the reaction time is 1-2h, most preferably 1h; after the addition is completed, the system is heated to 100-120°C, and the solvent in the system is removed at the same time, most preferably 110±5°C, and / or the reaction time is 30min-1h, most preferably 30min; after the solvent is completely removed, the protective gas is filled and the temperature is raised to 150-170°C, preferably 160±5°C, and / or the reaction is carried out for 4-5h, most preferably 5h; and / or, after the reaction is completed, the precipitant added to the system is ethanol; and / or the method of separating the solid is centrifugation, preferably centrifugation at 12000-15000rpm for 5-15min.

[0020] In a second aspect, the present invention provides nanoparticles obtained by the preparation method described in the first aspect.

[0021] In a third aspect, the present invention provides the use of the nanoparticles described in the second aspect in preparing inks, especially anti-counterfeiting packaging inks.

[0022] In a fourth aspect, the present invention provides an ink, the composition of the ink by mass percentage includes: 0.1-1.5% of the nanoparticles according to claim 12, 3-6% of a polyurethane / polyacrylic acid emulsion, 10-14% of a cosolvent, 0.5-1% of a surfactant, 0.2-0.6% of a moisturizer, and the remainder is water.

[0023] Preferably, the cosolvent is selected from at least one of ethanol, methanol, isopropanol, propylene oxide and glycerol, more preferably glycerol; and / or, the surfactant is selected from at least one of sodium stearate, isotridecyl stearate, pentaerythritol stearate, hydroxyethyl cellulose, polysorbate and cetearyl stearate; and / or, the humectant is selected from at least one of urea, ethylenediamine, amino acids and casein peptone.

[0024] Preferably, the preparation method of the polyurethane / polyacrylic acid emulsion comprises the following steps:

[0025] 1) preparing a hydrophilic polyurethane prepolymer dispersion: using polytetramethylene glycol and p-phenylene diisocyanate as basic raw materials, carrying out an addition reaction under the action of a catalyst, and then adding a hydrophilic chain extender to carry out a chain extension reaction to obtain a hydrophilic polyurethane prepolymer dispersion;

[0026] 2) adding butyl acrylate to the hydrophilic polyurethane prepolymer dispersion, and then adding an emulsifier and an initiator to carry out a polymerization reaction to obtain the polyurethane / polyacrylic acid emulsion.

[0027] Further preferably, in the step 1), the molar ratio of polytetramethylene glycol to p-phenylene diisocyanate is 1:1.8-2.2; and / or the catalyst is dibutyltin dilaurate, and the final concentration in the reaction system is 0.2 mg / ml-2 mg / ml; the hydrophilic chain extender is 1,4-butanediol and bisphenol-A compounded in a mass ratio of 1:2-3, and the final concentration in the reaction system is 0.2 mg / ml-0.5 mg / ml.

[0028] Further preferably, in the step 1), the addition reaction temperature is 70 to 90° C., more preferably 75 to 85° C.; and / or, the addition reaction time is 2 to 8 hours, more preferably 4 to 6 hours; and / or, the pH value of the addition reaction system is 4 to 9, preferably 6 to 8; and / or,

[0029] The chain extension reaction temperature is 60 to 90° C., more preferably 70 to 80° C.; and / or, the chain extension reaction time is 2 to 8 hours, preferably 4 to 6 hours; and / or, the chain extension reaction system pH value is 4 to 9, more preferably 6 to 8;

[0030] More preferably, the reagent used to adjust the pH value of the addition reaction system or the pH value of the chain extension reaction system is selected from one or more of triethylamine, tripropylamine or 2-methylethanolamine, and triethylamine is most preferred.

[0031] Further preferably, in the step 2), the emulsifier is selected from one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or sodium alkyl sulfonate, and sodium dodecyl sulfate is most preferred; the amount of the emulsifier is 0.5-3% by weight of butyl acrylate, preferably 1-2% by weight of butyl acrylate; and / or,

[0032] The initiator is selected from azobisisobutyronitrile, potassium sulfate, ammonium persulfate or dibenzoyl peroxide, preferably azobisisobutyronitrile; the amount of the initiator is 0.5-3% by weight of butyl acrylate, and most preferably 1-2% by weight of butyl acrylate.

[0033] Further preferably, in the step 2), the polymerization reaction temperature is 60-90° C., more preferably 70-85° C.; and / or the polymerization reaction time is 2-8 h, more preferably 2-6 h; and / or the pH value of the polymerization reaction system is 4-9, preferably 6-8; more preferably, the reagent used to adjust the pH value of the polymerization reaction system is sodium bicarbonate or sodium carbonate, most preferably sodium bicarbonate.

[0034] In a fifth aspect, the present invention provides a method for preparing the ink described in the fourth aspect, comprising: preparing ingredients according to the components of the ink, and then mixing all the components evenly to obtain the ink.

[0035] In a sixth aspect, the present invention provides use of the ink described in the fourth aspect in preparing information anti-counterfeiting products.

[0036] More specifically, the ink is used as fluorescent ink to make anti-counterfeiting products. Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0037] (1) The present invention uses polyacrylic acid to modify the surface of lanthanide rare earth doped NaYF4 upconversion nanoparticles to obtain a nanoparticle, and the nanomaterial has the characteristics of small size, large specific surface area, and a large number of rare earth ion luminescence centers on the surface. During the excitation process of the nanoparticle, these exposed luminescence centers easily exchange energy with organic ligands or solvents on the surface, so that the excitation energy emits strong fluorescence. Therefore, the nanoparticle also has the advantages of high luminescence efficiency and strong fluorescence intensity.

[0038] (2) The nanoparticles of the present invention can be used to prepare plant oil-based fluorescent inks. The anti-counterfeiting inks obtained have the advantages of no organic solvent volatilization, no radioactive elements, no toxicity, and good environmental protection. The inks are uniform and stable, have strong acid and alkali resistance, and meet the performance standards of relevant industries. They also have the advantages of high fluorescence intensity, good color rendering, beautiful printed patterns, and sustainable luminescence.

[0039] (3) The ink of the present invention is used to prepare anti-counterfeiting products. The implementation process is simple, the concealment is good, the inspection is convenient, and the printing conditions are less restricted. It is suitable for printing methods such as screen printing, offset printing, and gravure printing, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The fluorescence intensity comparison of the lanthanide rare earth doped NaYF4 upconversion nanomaterials modified with polyacrylic acid (PAA) in Example 3 and unmodified in Comparative Example 3 is shown.

[0041] Figure 2 The emission spectra of the PAA-modified lanthanide rare earth-doped NaYF4 upconversion nanomaterial prepared in Example 3 at excitation wavelengths of 370 nm (a) and 980 nm (b).

[0042] Figure 3 This is the particle size distribution of the PAA-modified lanthanide rare earth-doped NaYF4 upconversion nanomaterial prepared in Example 3.

[0043] Figure 4 This is a transmission electron microscope morphology image of the PAA-modified lanthanide rare earth-doped NaYF4 upconversion nanomaterial in Example 3.

[0044] Figure 5 This is a transmission electron microscope morphology of the lanthanide rare earth doped NaYF4 upconversion nanomaterial in Comparative Example 1 that has not been modified by PAA.

[0045] Figure 6 The thixotropic properties of the lanthanide rare earth doped NaYF4 upconversion nanomaterial-based ink in Comparative Example 1 that has not been modified by PAA.

[0046] Figure 7 This is the thixotropic property of the PAA-modified lanthanide rare earth-doped NaYF4 upconversion nanomaterial-based ink in Example 3. DETAILED DESCRIPTION

[0047] It should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturers are not specified, are all conventional products that can be purchased commercially.

[0048] The present invention is further described in detail below in conjunction with the accompanying drawings and specific preferred embodiments, which are intended to explain the present invention rather than to limit it.

[0049] A specific embodiment of the present invention provides a method for preparing nanoparticles, which is obtained by surface modifying lanthanide rare earth-doped NaYF4 upconversion nanoparticles with polyacrylic acid, wherein the mass ratio of the polyacrylic acid to the lanthanide rare earth-doped NaYF4 upconversion nanoparticles is 1:5-50.

[0050] One preferred method of preparing lanthanide rare earth doped NaYF4 upconversion nanoparticles of the present invention comprises the following steps:

[0051] (1) Preparing a rare earth oleate precursor: mixing yttrium salt, rare earth metal salt and oleic acid compound in solvent three, heating and reacting to obtain a rare earth oleate precursor;

[0052] (2) Preparation of lanthanide rare earth doped NaYF4 upconversion nanoparticles: The rare earth oleate precursor, oleic acid, octadecene, ammonium fluoride and a catalyst are mixed and reacted, and after the reaction is completed, a solid is separated to obtain the nanoparticles.

[0053] In the step (1), the yttrium salt is selected from YCl3; the rare earth metal salt is selected from YbCl3 or ErCl3; the oleic acid compound is selected from one of sodium oleate, potassium oleate, oleic acid, and egg yolk lecithin; the molar ratio of the yttrium salt, the rare earth metal salt, and the oleic acid compound is: 1-7: 0.1-1: 5-7; the solvent three is a mixture of water and at least one of methanol, ethanol, isopropanol, and ethylene oxide, and at least one of n-hexane, n-heptane, isohexane, and petroleum ether. The temperature of the heating reaction is 60-80°C, and the reaction time is 3-6h.

[0054] In the step (2), rare earth oleate precursor, oleic acid and octadecene are mixed, and ammonium fluoride and catalyst are added to solvent four for mixing, and then the two liquids are mixed and reacted; the molar ratio of rare earth oleate precursor, ammonium fluoride and catalyst is 1-10:2-12:1-15; the catalyst is sodium hydroxide or potassium hydroxide; the solvent four is selected from at least one of methanol, ethanol, dichloromethane and chloroform. The control procedure of the mixed reaction includes: during the addition of the mixed liquid of ammonium fluoride, catalyst and solvent four, the system temperature is 40-60°C and the reaction time is 1-2h; after the addition is completed, the system is heated to 100-120°C, and the solvent in the system is removed at the same time, and the reaction time is 30min-1h; after the solvent is completely removed, protective gas is filled and the temperature is raised to 300-320°C, and the reaction is carried out for 4-5h; after the reaction is completed, ethanol is added to the system for precipitation, and then centrifuged at 12000-15000rpm for 5-15min to separate the solid.

[0055] One preferred method of surface modification of the present invention comprises the following steps:

[0056] Step 1, adding the lanthanide rare earth doped NaYF4 upconversion nanoparticles to solvent 1 and mixing to obtain an upconversion nanoparticle solution, and dissolving polyacrylic acid in solvent 2 and mixing to obtain a polyacrylic acid solution;

[0057] Step 2, mixing the upconversion nanoparticle solution and the polyacrylic acid solution at 20-30° C. for 20-30 hours, separating the solid after the reaction, and drying to obtain the nanoparticles;

[0058] The first solvent is selected from at least one of cyclohexane, n-hexane, dimethylformamide, dimethyl carbonate, and dichloromethane; the second solvent is selected from at least one of ethanol, acetone, and isopropanol.

[0059] In the step 2, the solid is separated by centrifugation at 12000-15000 rpm for 5-15 minutes; and vacuum drying is performed at 50-70° C. and a vacuum degree of not less than 0.05 MPa for 2-3 hours.

[0060] The nanoparticles obtained by the above preparation method are further prepared into plant oil-based fluorescent ink. The obtained ink is uniform and stable, has strong acid and alkali resistance, and also has the advantages of high fluorescence intensity, good color rendering, beautiful printed pattern effect, and sustainable luminescence.

[0061] In addition, the plant oil-based fluorescent ink also contains an aqueous polyurethane / polyacrylic acid emulsion, in which a block copolymer phase separation will occur, thereby forming an optical anti-counterfeiting phenomenon. Different from the rare earth element fluorescent anti-counterfeiting mechanism, the polyacrylic acid emulsion can regulate the soft / hard segments of the aqueous polyurethane molecular chain, thereby forming a microphase separation to form a periodic light wave layer, and the multilayer configuration plays the role of a Bragg reflector. Depending on the difference in the refractive index and layer thickness of the hydrophilic and hydrophobic components of the aqueous polyurethane, it can diffract a certain wavelength of light, thereby forming an anti-counterfeiting coating. The most preferred embodiment of the method for preparing the polyurethane / polyacrylic acid emulsion of the present invention is provided below. This method does not constitute a process limitation for preparing the aqueous polyurethane / polyacrylic acid emulsion of the present invention. As long as it is within the range of the reagents, ratios, process parameters, etc. disclosed in the present invention, an aqueous polyurethane / polyacrylic acid emulsion can be obtained, and it has the aforementioned functions. The most preferred preparation method includes the following steps:

[0062] 1) preparing a hydrophilic polyurethane prepolymer dispersion: using polytetramethylene glycol and p-phenylene diisocyanate as basic raw materials, carrying out an addition reaction under the action of a catalyst, and then adding a hydrophilic chain extender to carry out a chain extension reaction to obtain a hydrophilic polyurethane prepolymer dispersion; wherein the molar ratio of polytetramethylene glycol to p-phenylene diisocyanate is 1:2; the catalyst is dibutyltin dilaurate, and the final concentration in the reaction system is 1 mg / ml; the hydrophilic chain extender is 1,4-butanediol and bisphenol-A compounded in a mass ratio of 1:2, and the final concentration in the reaction system is 0.5 mg / ml;

[0063] The addition reaction temperature is 80±2℃; the addition reaction time is 5h; the pH value of the addition reaction system is 7.

[0064] The chain extension reaction temperature is 75±2℃; the chain extension reaction time is 5h; the pH value of the chain extension reaction system is 7;

[0065] The pH value was adjusted with triethylamine.

[0066] 2) Adding butyl acrylate to the hydrophilic polyurethane prepolymer dispersion, and then adding an emulsifier and an initiator to carry out a polymerization reaction to obtain a polyurethane / polyacrylic acid emulsion.

[0067] The emulsifier is sodium dodecyl sulfate, and the amount used is 2% by weight of butyl acrylate; the initiator is azobisisobutyronitrile, and the amount used is 2% by weight of butyl acrylate;

[0068] The polymerization reaction temperature is 80±2°C; the polymerization reaction time is 5h; the pH value of the polymerization reaction system is 7; and the pH value is adjusted by sodium bicarbonate.

[0069] The polyurethane / polyacrylic acid emulsion used in the following examples is obtained by the aforementioned most preferred embodiment.

[0070] Example 1

[0071] This embodiment provides a method for preparing ink, which comprises the following steps:

[0072] 1. Synthesis of rare earth oleate precursor: In a 100mL round-bottom flask, add 1.0g (6.2mmol) YCl3, 0.5g (1.2mmol) YbCl3, 0.01g (0.03mmol) ErCl3, 1.2g (5.0mmol) sodium oleate, 6mL deionized water, 7mL ethanol and 14mL n-hexane. Stir the whole system evenly and place it in a 70℃ water bath for reflux reaction for 4h. After the reaction is completed, wash it three times with deionized water (20mL×3) to remove the by-product NaCl. Collect the organic phase, remove the n-hexane by rotary evaporation, and obtain a waxy solid, i.e., a rare earth precursor.

[0073] 2. Lanthanide rare earth doped NaYF4 upconversion nanomaterials: In a 100mL three-necked flask, add 10mmol (5.8g) of rare earth precursor, 12mL of oleic acid and 30mL of octadecene in sequence. Stir the whole system evenly, and heat it to 140℃ under vacuum to remove the low boiling point solvent in the system to obtain a transparent solution, and cool it to 50℃. Subsequently, add 20mL of methanol solution containing 1.5g (15.0mmol) of NaOH and 1.0g (12.0mmol) of NH4F to the system. With the addition of methanol solution, the transparent liquid in the three-necked flask gradually becomes turbid, and the system continues to stir and react at 50℃ for 1h. After the reaction is completed, the system is heated to 110℃ and maintained for 30min, and vacuum is evacuated to remove methanol in the system. After the methanol is completely removed, argon is filled into the system and the temperature is raised to 160℃, and refluxed for 5h. After the reaction is completed, the system is naturally cooled to 25℃, and 40mL of ethanol is added for precipitation. The particles were collected by centrifugation (14000 rpm, 10 min) and washed three times (30 mL × 3) with a mixed solution of ethanol and cyclohexane (volume ratio of 4:1). Finally, the obtained NaYF4:Yb,Er upconversion nanoparticles were redispersed in 10 mL of cyclohexane for later use.

[0074] 3. PAA-modified lanthanide rare earth doped NaYF4 upconversion nanomaterials: Using polyacrylic acid PAA as the exchange ligand, replacing NaYF4:Ln 3+ Oleic acid ligands on the surface of upconversion nanoparticles to obtain PAA-encapsulated hydrophilic NaYF4:Ln 3+ Upconversion nanoparticles (PAA-NaYF4:Ln 3+ The specific experimental process is as follows: In a 50mL round-bottom flask, add 10mL of 0.2gNaYF4:Er 3+ The cyclohexane solution of upconversion nanoparticles and 10 mL of ethanol solution containing 1.0 g of PAA were stirred at 25 ° C for 24 h. After the reaction, the product was centrifuged (14000 rpm, 10 min), washed three times with ethanol and deionized water (10 mL × 3), and dried in vacuum at 60 ° C to obtain hydrophilic PAA-NaYF4:Ln 3+ Nanoparticles.

[0075] 4. By mass percentage, 0.1% PAA modified lanthanide-doped PAA-NaYF4:Ln 3+ , 6% polyurethane / polyacrylic acid emulsion, 10% ethanol, 1% sodium stearate, 0.6% urea and the remainder of water were mixed evenly, and then the above solution was magnetically stirred for 20 minutes and then ultrasonically treated for 10 minutes to obtain the anti-counterfeiting fluorescent ink.

[0076] Example 2

[0077] This embodiment provides a method for preparing ink, which comprises the following steps:

[0078] 1. Synthesis of rare earth oleate precursor: In a 100mL round-bottom flask, add 0.5g (2.0mmol) YCl3, 0.2g (0.5mmol) YbCl3, 0.01g (0.03mmol) ErCl3, 1.5g (5.5mmol) sodium oleate, 6mL deionized water, 7mL ethanol and 14mL n-hexane. Stir the whole system evenly and place it in a 70℃ water bath for reflux reaction for 4h. After the reaction is completed, wash it three times with deionized water (20mL×3) to remove the by-product NaCl. Collect the organic phase, remove the n-hexane by rotary evaporation, and obtain a waxy solid, i.e., a rare earth precursor.

[0079] 2. Lanthanide rare earth doped NaYF4 upconversion nanomaterials: In a 100mL three-necked flask, 3mmol (2.6g) of rare earth precursor, 12mL of oleic acid and 30mL of octadecene were added in sequence. The whole system was stirred evenly and heated to 140°C under vacuum to remove the low boiling point solvent in the system to obtain a transparent solution, which was then cooled to 50°C. Subsequently, 20mL of methanol solution containing 0.25g (5.0mol) of NaOH and 0.25g (7.0mmol) of NH4F was added to the system. With the addition of the methanol solution, the transparent liquid in the three-necked flask gradually became turbid, and the system continued to stir and react at 50°C for 1h. After the reaction was completed, the system was heated to 110°C for 30min, and the system was vacuumed to remove the methanol in the system. After the methanol was completely removed, argon was filled into the system and the temperature was raised to 160°C, and the reaction was refluxed for 5h. After the reaction was completed, the system was naturally cooled to 25°C, and 40mL of ethanol was added for precipitation. The particles were collected by centrifugation (14000 rpm, 10 min) and washed three times (30 mL × 3) with a mixed solution of ethanol and cyclohexane (volume ratio of 4:1). Finally, the obtained NaYF4:Yb,Er upconversion nanoparticles were redispersed in 10 mL of cyclohexane for later use.

[0080] 3. PAA-modified lanthanide rare earth doped NaYF4 upconversion nanomaterials: Using polyacrylic acid PAA as the exchange ligand, replacing NaYF4:Ln 3+ Oleic acid ligands on the surface of upconversion nanoparticles to obtain PAA-encapsulated hydrophilic NaYF4:Ln 3+ Upconversion nanoparticles (PAA-NaYF4:Ln 3+ The specific experimental process is as follows: In a 50 mL round-bottom flask, add 10 mL of 0.1 g NaYF4:Ln 3+The cyclohexane solution of upconversion nanoparticles and 10 mL of ethanol solution containing 1.5 g of PAA were stirred at 25 °C for 24 h. After the reaction, the product was centrifuged (14000 rpm, 10 min), washed three times with ethanol and deionized water (10 mL × 3), and dried in vacuum at 60 °C to obtain hydrophilic PAA-NaYF4:Ln 3+ Nanoparticles.

[0081] 4. By mass percentage, 1.5% PAA modified lanthanide-doped PAA-NaYF4:Ln 3+ , 3% polyurethane / polyacrylic acid emulsion, 14% ethanol, 0.5% sodium stearate, 0.2% urea and the remainder of water were mixed evenly, and then the above solution was magnetically stirred for 20 minutes and then ultrasonically treated for 10 minutes to obtain the anti-counterfeiting fluorescent ink.

[0082] Example 3

[0083] This embodiment provides a method for preparing ink, which comprises the following steps:

[0084] 1. Synthesis of rare earth oleate precursor: In a 100mL round-bottom flask, add 0.4732g (1.56mmol) YCl3, 0.1549g (0.40mmol) YbCl3, 0.0158g (0.04mmol) ErCl3, 1.8570g (6.1mmol) sodium oleate, 6mL deionized water, 7mL ethanol and 14mL n-hexane. Stir the whole system evenly and place it in a 70℃ water bath for reflux reaction for 4h. After the reaction is completed, wash it three times with deionized water (20mL×3) to remove the by-product NaCl. Collect the organic phase, remove the n-hexane by rotary evaporation, and obtain a waxy solid, i.e., a rare earth precursor.

[0085] 2. Lanthanide rare earth doped NaYF4 upconversion nanomaterials: In a 100mL three-necked flask, add 2mmol (1.900g) of rare earth precursor, 12mL of oleic acid and 30mL of octadecene in sequence. Stir the whole system evenly, and heat to 140℃ under vacuum to remove the low boiling point solvent in the system to obtain a transparent solution, and cool to 50℃. Subsequently, add 20mL of methanol solution containing 0.2000g (5.0mmol) of NaOH and 0.2963g (8.0mmol) of NH4F to the system. With the addition of methanol solution, the transparent liquid in the three-necked flask gradually becomes turbid, and the system continues to stir and react at 50℃ for 1h. After the reaction is completed, heat the system to 110℃ and keep it for 30min, and evacuate to remove methanol in the system. After the methanol is completely removed, fill the system with argon and heat it to 310℃, and reflux for 5h. After the reaction was completed, the system was naturally cooled to 25°C and 40 mL of ethanol was added for precipitation. The particles were collected by centrifugation (14000 rpm, 10 min) and washed three times (30 mL × 3) with a mixed solution of ethanol and cyclohexane (volume ratio of 4:1). Finally, the obtained NaYF4:Yb,Er upconversion nanoparticles were redispersed in 10 mL of cyclohexane for later use.

[0086] 3. PAA-modified lanthanide rare earth doped NaYF4 upconversion nanomaterials: Using polyacrylic acid PAA as the exchange ligand, replacing NaYF4:Ln 3+ Oleic acid ligands on the surface of upconversion nanoparticles to obtain PAA-encapsulated hydrophilic NaYF4:Ln 3+ Upconversion nanoparticles (PAA-NaYF4:Ln 3+ The specific experimental process is as follows: In a 50 mL round-bottom flask, add 10 mL of 0.15 g NaYF4:Ln 3+ The cyclohexane solution of upconversion nanoparticles and 10 mL of ethanol solution containing 1.58 g of PAA were stirred at 25 ° C for 24 h. After the reaction, the product was centrifuged (14000 rpm, 10 min), washed three times with ethanol and deionized water (10 mL × 3), and dried in vacuum at 60 ° C to obtain hydrophilic PAA-NaYF4:Ln3+ nanoparticles.

[0087] 4. By mass percentage, 1.0% PAA modified lanthanide-doped PAA-NaYF4:Ln 3+ , 5% polyurethane / polyacrylic acid emulsion, 12% ethanol, 0.8% sodium stearate, 0.4% urea and the remainder of water were mixed evenly, and then the above solution was magnetically stirred for 20 minutes and then ultrasonically treated for 10 minutes to obtain the anti-counterfeiting fluorescent ink.

[0088] Comparative Example 1

[0089] This comparative example provides a method for preparing an ink, which comprises the following steps:

[0090] 1. Synthesis of rare earth oleate precursor: In a 100mL round-bottom flask, add 0.4732g (1.56mmol) YCl3, 0.1549g (0.40mmol) YbCl3, 0.0158g (0.04mmol) ErCl3, 1.8570g (6.1mmol) sodium oleate, 6mL deionized water, 7mL ethanol and 14mL n-hexane. Stir the whole system evenly and place it in a 70℃ water bath for reflux reaction for 4h. After the reaction is completed, wash it three times with deionized water (20mL×3) to remove the by-product NaCl. Collect the organic phase, remove the n-hexane by rotary evaporation, and obtain a waxy solid, i.e., a rare earth precursor.

[0091] 2. Lanthanide rare earth doped NaYF4 upconversion nanomaterials: In a 100mL three-necked flask, add 2mmol (1.900g) of rare earth precursor, 12mL of oleic acid and 30mL of octadecene in sequence. Stir the whole system evenly, and heat to 140℃ under vacuum to remove the low boiling point solvent in the system to obtain a transparent solution, and cool to 50℃. Subsequently, add 20mL of methanol solution containing 0.2000g (5.0mmol) of NaOH and 0.2963g (8.0mmol) of NH4F to the system. With the addition of methanol solution, the transparent liquid in the three-necked flask gradually becomes turbid, and the system continues to stir and react at 50℃ for 1h. After the reaction is completed, heat the system to 110℃ and keep it for 30min, and evacuate to remove methanol in the system. After the methanol is completely removed, fill the system with argon and heat it to 310℃, and reflux for 5h. After the reaction was completed, the system was naturally cooled to 25°C and 40 mL of ethanol was added for precipitation. The particles were collected by centrifugation (14000 rpm, 10 min) and washed three times (30 mL × 3) with a mixed solution of ethanol and cyclohexane (volume ratio of 4:1). Finally, the obtained NaYF4:Yb,Er upconversion nanoparticles were redispersed in 10 mL of cyclohexane for later use.

[0092] 3. By mass percentage, 1.0% unmodified lanthanide-doped NaYF4:Ln 3+ , 5% polyurethane / polyacrylic acid emulsion, 12% ethanol, 0.8% sodium stearate, 0.4% urea and the remainder of water were mixed evenly, and then the above solution was magnetically stirred for 20 minutes and then ultrasonically treated for 10 minutes to obtain the anti-counterfeiting fluorescent ink.

[0093] Figure 1The fluorescence intensity of the lanthanide rare earth doped NaYF4 upconversion nanomaterial modified by PAA in Example 3 is compared with that of the unmodified lanthanide rare earth doped NaYF4 upconversion nanomaterial in Comparative Example 3. As can be seen from the figure, the fluorescence intensity of the lanthanide rare earth doped NaYF4 upconversion nanomaterial modified by PAA is greatly improved. Since the fluorescence peak position and fluorescence intensity of the lanthanide rare earth doped NaYF4 upconversion nanomaterial modified by PAA in Examples 1 and 2 are consistent with the fluorescence peak position and fluorescence intensity of the lanthanide rare earth doped NaYF4 upconversion nanomaterial modified by PAA in Example 3, only the relevant results of Example 3 are given. Figures 2 to 7 The relevant test also only gives the relevant results of Example 3, and Example 1 and Example 2 are similar to Example 3.

[0094] Figure 2 The emission spectra of the lanthanide rare earth doped NaYF4 upconversion nanomaterial prepared in Example 3 at excitation wavelengths of 370nm and 980nm respectively. As can be seen from the figure, under excitation of 370nm ultraviolet wavelength, an emission peak appears at 430nm, and blue fluorescence emission is obtained; under excitation of 980nm near-infrared wavelength, an emission peak appears at 525nm, and green fluorescence emission is obtained.

[0095] Figure 3 The particle size distribution of the lanthanide rare earth doped NaYF4 upconversion nanomaterial prepared in Example 3. As can be seen from the figure, the particle size of the upconversion nanomaterial is between 30nm and 40nm, and the average particle size is 33.5nm.

[0096] Figure 4 This is a transmission electron microscope image of the PAA-modified lanthanide rare earth-doped NaYF4 upconversion nanomaterial in Example 3. It can be seen from the image that the morphology of the modified material is uniform nano-round particles.

[0097] Figure 5 This is a transmission electron microscope image of the lanthanide rare earth doped NaYF4 upconversion nanomaterial in Comparative Example 3 that has not been modified by PAA. It can be seen from the image that although the unmodified material is also round particles, they are of different sizes and the particles are uneven.

[0098] Figure 6 The thixotropic properties of the unmodified ink in Comparative Example 3, where low shear 1: rate 2 mN.s -1 , 60s in total, simulating the ink static time; High shear 2: rate 100mN.s -1 , 15s in total, simulating scraper channel; low shear 3: rate 2mN.s -1, a total of 35s, simulating the reorganization of the ink after printing. As can be seen from the figure, 0-60s is the first low shear, 60-75s is the second high shear, and 75-110s is the third low shear. It can be seen that the viscosity of the ink without adding nanofibril cellulose does not change with the change of shear rate, reflecting the properties of typical Newtonian fluids, which is not friendly to water-based inks.

[0099] Figure 7 The thixotropic properties of the PAA-modified ink in Example 3, where low shear 1: rate 2 mN.s -1 , 60s in total, simulating the ink static time; High shear 2: rate 1000mN.s -1 , 15s in total, simulating scraper channel; low shear 3: rate 2mN.s -1 , a total of 200s, simulating the reorganization of the ink after printing. As can be seen from the figure, after adding nanofibril cellulose, the ink shows a certain shear thinning property, becoming a typical non-Newtonian fluid. When the ink is subjected to high-speed shear, its viscosity decreases, the fluidity is good, and it is easy to transfer; when the ink is transferred to the paper, the external force suddenly disappears, and the viscosity suddenly increases, protecting the ink from overflowing to the surrounding area, so that it has good printability on the substrate.

[0100] For the ink prepared from the unmodified lanthanide rare earth doped NaYF4 upconversion nanomaterial in Comparative Example 3, the ink is very easy to fall off when printed on plastic during the printing process. The reason may be that the numerous groups on the surface of the unmodified upconversion nanomaterial adsorb many pigments, and thus the ink is not tightly bonded to the surface of the substrate, which is very unfavorable for the printing operation. Therefore, the ink of the present invention has better printing adaptability.

[0101] In summary, the present invention uses oleic acid rare earth salt as a precursor and adopts thermal decomposition method to prepare NaYF4:Ln 3+ Upconversion nanoparticles, by rationally doping different lanthanide ions and adjusting the molar ratio of the doped lanthanide ions, obtain the red, green and blue primary colors of NaYF4:Ln 3+ Upconversion nanoparticles. The surface of the synthesized NaYF4 upconversion nanoparticles was modified by PAA ligand exchange to obtain hydrophilic NaYF4 upconversion nanoparticles wrapped by waterborne polyurethane / polyacrylic acid. The obtained hydrophilic nanoparticles were used as fluorescent fillers and anti-counterfeiting packaging fluorescent ink was prepared using waterborne polyurethane / polyacrylic acid emulsion as solvent. The advantages of the present invention are:

[0102] (1) The lanthanide-doped NaYF4 anti-counterfeiting fluorescent ink prepared by the present invention belongs to a colloidal dispersion system, which includes pigment particles of a dispersed phase and a binder sol of a connecting phase. Due to the characteristics of the interface between the two phases, it has relatively good stability and avoids the aggregation and sedimentation of the particles. The mixing of a solvent containing an unsaturated bond in the system will increase its unsaturation and accelerate the drying speed of the system in the oxidation film stage.

[0103] (2) The nanomaterials in the lanthanide-doped NaYF4 anti-counterfeiting fluorescent ink prepared by the present invention are small in size and large in specific surface area, which results in the presence of a large number of rare earth ion luminescence centers on the surface of the upconversion nanoparticles. During the excitation process, these luminescence centers in the exposed state easily exchange energy with the organic ligands or solvents on the surface, so that the excitation energy emits strong fluorescence. In addition, the rare earth upconversion fluorescent system is a multi-level system. During the excitation process, adjacent ions cross each other, resulting in a higher luminescence efficiency of the material and enhanced fluorescence intensity.

[0104] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing nanoparticles, characterized in that: include: The surface of lanthanide rare earth doped NaYF4 upconversion nanoparticles is modified by polyacrylic acid, wherein the mass ratio of the lanthanide rare earth doped NaYF4 upconversion nanoparticles to the polyacrylic acid is 1:5-50.

2. The preparation method according to claim 1, characterized in that: The surface modification comprises the following steps: Step 1, adding the lanthanide rare earth doped NaYF4 upconversion nanoparticles to solvent 1 to obtain an upconversion nanoparticle solution, and dissolving polyacrylic acid in solvent 2 to obtain a polyacrylic acid solution; and Step 2: mixing the upconversion nanoparticle solution and the polyacrylic acid solution at 20-30° C. for reaction for 20-30 hours, separating the solid after the reaction, and drying to obtain the nanoparticles.

3. The preparation method according to claim 2, characterized in that: The first solvent is selected from at least one of cyclohexane, n-hexane, dimethylformamide, dimethyl carbonate and dichloromethane; and / or the second solvent is selected from at least one of ethanol, acetone and isopropanol.

4. The preparation method according to claim 2, characterized in that: In the step 2, the volume ratio of the upconversion nanoparticle solution to the polyacrylic acid solution is 1:2-4; and / or, the method for separating the solid is centrifugation, preferably centrifugation at 12000-15000 rpm for 5-15 min; and / or, the method for drying is vacuum drying, preferably drying at 50-70° C. and a vacuum degree of not less than 0.05 MPa for 2-3 h.

5. The preparation method according to any one of claims 2 to 4, characterized in that: The preparation method of the lanthanide rare earth doped NaYF4 upconversion nanoparticles comprises the following steps: (1) preparing a rare earth oleate precursor: mixing yttrium salt, rare earth metal salt, and oleic acid compound in solvent three, heating and reacting to obtain a rare earth oleate precursor; and (2) Preparation of lanthanide rare earth doped NaYF4 upconversion nanoparticles: The rare earth oleate precursor, oleic acid, octadecene, ammonium fluoride and a catalyst are mixed and reacted. After the reaction is completed, a precipitant is added to the system and a solid is separated to obtain the lanthanide rare earth doped NaYF4 upconversion nanoparticles.

6. The preparation method according to claim 5, characterized in that: In the step (1), the yttrium salt is selected from YCl3; the rare earth metal salt is selected from YbCl3 and / or ErCl3; the oleic acid compound is selected from one of sodium oleate, potassium oleate, oleic acid and egg yolk lecithin; preferably, the molar ratio of the yttrium salt, the rare earth metal salt and the oleic acid compound is: 1-7:0.1-1.5:5-7.

7. The preparation method according to claim 5 or 6, characterized in that: In the step (1), the solvent three is a mixture of water and at least one selected from methanol, ethanol, isopropanol and ethylene oxide, and at least one selected from n-hexane, n-heptane, isohexane and petroleum ether; preferably, the solvent three is a mixture of deionized water and at least one selected from methanol and ethanol, and at least one selected from n-hexane and isohexane; more preferably, the solvent three is a mixture of deionized water, ethanol and n-hexane in a volume ratio of 1-2:1-2:1-4.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In the step (1), the heating reaction temperature is 60 to 80° C., preferably 70±5° C.; and / or the reaction time is 3 to 6 hours, preferably 4 to 5 hours.

9. The preparation method according to any one of claims 5 to 8, characterized in that: In the step (2), a rare earth oleate precursor, oleic acid and octadecene are mixed to obtain a first mixed solution, and ammonium fluoride and a catalyst are added to solvent four to obtain a second mixed solution, and then the two mixed solutions are mixed to react; preferably, the molar ratio of the rare earth oleate precursor, ammonium fluoride and the catalyst is 1-10:2-12:1-15.

10. The preparation method according to claim 9, characterized in that: The catalyst is sodium hydroxide or potassium hydroxide; and / or the solvent is selected from at least one of methanol, ethanol, dichloromethane and chloroform.

11. The preparation method according to claim 9 or 10, characterized in that: In the step (2), the control procedure of the mixed reaction includes: during the addition of the mixed solution of ammonium fluoride, the catalyst and the solvent four, the system temperature is 40-60°C, preferably 50±5°C, and / or the reaction time is 1-2h, preferably 1h; after the addition is completed, the system is heated to 100-120°C, and the solvent in the system is removed at the same time, preferably the temperature is 110±5°C, and / or the reaction time is 30min-1h, preferably 30min; after the solvent is completely removed, the protective gas is filled and the temperature is raised to 150-170°C, preferably 160±5°C, and / or the reaction is carried out for 4-5h, preferably 5h; and / or, after the reaction is completed, the precipitant added to the system is ethanol; and / or, the method for separating the solid is centrifugation, preferably centrifugation at 12000-15000rpm for 5-15min.

12. Nanoparticles obtained by the preparation method according to any one of claims 1 to 11.

13. Use of the nanoparticles according to claim 12 in the preparation of inks, especially in anti-counterfeiting packaging inks.

14. An ink, characterized in that: The ink comprises, by mass percentage, 0.1-1.5% of the nanoparticles according to claim 12, 3-6% of polyurethane / polyacrylic acid emulsion, 10-14% of cosolvent, 0.5-1% of surfactant, 0.2-0.6% of moisturizer, and the balance is water.

15. The ink according to claim 14, characterized in that The cosolvent is selected from at least one of ethanol, methanol, isopropanol, propylene oxide and glycerol, preferably glycerol; and / or, the surfactant is selected from at least one of sodium stearate, isotridecyl stearate, pentaerythritol stearate, hydroxyethyl cellulose, polysorbate and cetyl stearate; and / or, the humectant is selected from at least one of urea, ethylenediamine, amino acids and casein peptone.

16. The ink according to claim 14 or 15, characterized in that: The preparation method of the polyurethane / polyacrylic acid emulsion comprises the following steps: 1) preparing a hydrophilic polyurethane prepolymer dispersion: using polytetramethylene glycol and p-phenylene diisocyanate as basic raw materials, carrying out an addition reaction under the action of a catalyst, and then adding a hydrophilic chain extender to carry out a chain extension reaction to obtain a hydrophilic polyurethane prepolymer dispersion; 2) adding butyl acrylate to the hydrophilic polyurethane prepolymer dispersion, and then adding an emulsifier and an initiator to carry out a polymerization reaction to obtain the polyurethane / polyacrylic acid emulsion.

17. The ink according to claim 16, characterized in that In the step 1), the molar ratio of polytetramethylene glycol to p-phenylene diisocyanate is 1:1.8-2.2; and / or the catalyst is dibutyltin dilaurate, and the final concentration in the reaction system is 0.2mg / ml-2mg / ml; the hydrophilic chain extender is 1,4-butanediol and bisphenol-A compounded in a mass ratio of 1:2-3, and the final concentration in the reaction system is 0.2mg / ml-0.5mg / ml.

18. The ink according to claim 16 or 17, characterized in that: In the step 1), the addition reaction temperature is 70 to 90° C., preferably 75 to 85° C.; and / or, the addition reaction time is 2 to 8 hours, preferably 4 to 6 hours; the pH value of the addition reaction system is 4 to 9, preferably 6 to 8; and / or, The chain extension reaction temperature is 60 to 90° C., preferably 70 to 80° C.; and / or, the chain extension reaction time is 2 to 8 hours, preferably 4 to 6 hours; and / or, the chain extension reaction system pH value is 4 to 9, preferably 6 to 8; Preferably, the reagent used to adjust the pH value of the addition reaction system or the pH value of the chain extension reaction system is selected from one or more of triethylamine, tripropylamine or 2-methylethanolamine, more preferably triethylamine.

19. The ink according to any one of claims 16 to 18, characterized in that: In the step 2), the emulsifier is selected from sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or sodium alkyl sulfonate, preferably sodium dodecyl sulfate; the amount of the emulsifier is 0.5-3% by weight of butyl acrylate, preferably 1-2% by weight of butyl acrylate; and / or, The initiator is selected from azobisisobutyronitrile, potassium sulfate, ammonium persulfate or dibenzoyl peroxide, preferably azobisisobutyronitrile; the amount of the initiator is 0.5-3% of the weight of butyl acrylate, preferably 1-2% of the weight of butyl acrylate.

20. The ink according to claim 19, characterized in that In the step 2), the polymerization reaction temperature is 60-90° C., preferably 70-85° C.; and / or the polymerization reaction time is 2-8 hours, preferably 2-6 hours; and / or the pH value of the polymerization reaction system is 4-9, preferably 6-8; preferably, the reagent used to adjust the pH value of the polymerization reaction system is sodium bicarbonate or sodium carbonate, preferably sodium bicarbonate.

21. The method for preparing the ink according to any one of claims 14 to 20, characterized in that: include: The ink is prepared by mixing the ingredients according to the components of the ink and then mixing all the components evenly.

22. Use of the ink according to any one of claims 14 to 20 in preparing information anti-counterfeiting products.

Citation Information

Patent Citations

  • Composite upconversion nanoprobe with multicolor luminescent spectrums and preparation method and application of composite upconversion nanoprobe

    CN104059669A

  • Upconversion fluorescent ink for inkjet printer and preparation method of upconversion fluorescent ink

    CN104371424A

  • Preparation method of acrylate grafted polyurethane emulsion

    CN109180873A

  • Preparation method and application of rare earth doped NaYF4 / carbon quantum dot dual-mode fluorescent nanocomposite

    CN109181687A

  • Water-based digital inkjet printing pigment ink and preparation method and application thereof

    CN110358359A

Cited By

  • Preparation of fluorescent silver nanocluster composite material and application of fluorescent silver nanocluster composite material in fluorescent ink

    CN120665586A